2008
DOI: 10.1007/s10350-007-9092-4
|View full text |Cite
|
Sign up to set email alerts
|

Topical Sucralfate Decreases Pain After Hemorrhoidectomy and Improves Healing: A Randomized, Blinded, Controlled Study

Abstract: Topical sucralfate significantly reduces pain at Days 7 and 14 after hemorrhoidectomy and promotes faster wound healing compared with that of a placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Unlike Gupta study we evaluated pain intensity at the 1 st and 3 rd days which give more data about early effect of the drugs. 12 In present study, sucralfate had significant effect on pain intensity even in the first post-operative day but against this, study by Mirani et al showed that topical sucralfate ointment (10%) has a significant analgesic effect and can reduce both acute and chronic pain after hemorrhoidectomy but its analgesic effect is not obvious before 24 hours. This difference me be explained by the frequency of application of the treatment as in Mirani study patients applied the ointment every 12 hours only unlike every 6 hours in our study, we think that more frequent application gives better effect.…”
Section: Discussionmentioning
confidence: 46%
“…Unlike Gupta study we evaluated pain intensity at the 1 st and 3 rd days which give more data about early effect of the drugs. 12 In present study, sucralfate had significant effect on pain intensity even in the first post-operative day but against this, study by Mirani et al showed that topical sucralfate ointment (10%) has a significant analgesic effect and can reduce both acute and chronic pain after hemorrhoidectomy but its analgesic effect is not obvious before 24 hours. This difference me be explained by the frequency of application of the treatment as in Mirani study patients applied the ointment every 12 hours only unlike every 6 hours in our study, we think that more frequent application gives better effect.…”
Section: Discussionmentioning
confidence: 46%
“…Recently Sucralfate has been also used for reducing postoperative pain and promoting wound healing after open hemorrhoidectomy (21), for the healing of burns or skin injuries (22) and in the clinical treatment of vaginal ulceration (23).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that this occurs due to stimulation of fibroblast growth factor, stimulation of granulation tissues, antibacterial activity or angiogenic properties. 30 Gupta et al showed a significant reduction in pain after haemorrhoidectomy with topical application of 3 grams sucralfate and reduced analgesia requirements especially after 7 and 14 days. 30 They also showed a superior wound healing after application of sucralfate.…”
Section: Local Anaestheticmentioning
confidence: 99%
“…30 Gupta et al showed a significant reduction in pain after haemorrhoidectomy with topical application of 3 grams sucralfate and reduced analgesia requirements especially after 7 and 14 days. 30 They also showed a superior wound healing after application of sucralfate. They concluded that the effects were mediated by sucralfate binding to mucosal surfaces and interaction with surface phospholipids which stimulates prostaglandins and increases mucosal blood flow.…”
Section: Local Anaestheticmentioning
confidence: 99%